2020
DOI: 10.1039/d0ra07469a
|View full text |Cite
|
Sign up to set email alerts
|

Divergent reactivity of divinylsilanes toward sulfonamides in different oxidative systems

Abstract: The products of NBS-induced halosulfonamidation of divinylsilanes undergo base-induced cyclization providing new heterocycles including the hitherto unknown 1,3,5-diazasilinanes in up to quantitative yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…By replacing acetonitrile with THF as a solvent, we hoped to synthesize amino esters, as was previously successfully completed in our works [ 18 , 19 ]. However, with allyl chloride, instead, the product of bromination, 1,2-dibromo-3-chloropropane 16 , was isolated in a low yield ( Scheme 10 ) indicating that triflamide is not involved in the reaction.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…By replacing acetonitrile with THF as a solvent, we hoped to synthesize amino esters, as was previously successfully completed in our works [ 18 , 19 ]. However, with allyl chloride, instead, the product of bromination, 1,2-dibromo-3-chloropropane 16 , was isolated in a low yield ( Scheme 10 ) indicating that triflamide is not involved in the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Amidines similar to 14 containing bromine at the β-position to the amidine nitrogen atom readily undergo base-induced intramolecular cyclization to afford 5-substituted 2-methyl-1-triflyl-4,5-dihydro-1 H -imidazolines in up to quantitative yield [ 16 , 19 , 20 , 21 ]. With this in mind, we examined the reaction of amidine 14 with potassium carbonate and triethylamine in acetonitrile and found that dehydrobromination did occur but, instead of the expected 5-cyanomethylimidazoline 24 , N-[3-cyanoprop-2-en-1-yl)]-N’- (triflyl)ethaneimidamide 25 was unexpectedly formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found only a few examples, including a hydroamination reaction of camphene with mesylamide 16 and the preparation and functionalization of a sultam derivative of camphene as a catalyst in asymmetric synthesis. [17][18][19][20][21] With this in mind, and given our continued interest in oxidative sulfonamidation, [22][23][24][25][26][27]…”
Section: Introductionmentioning
confidence: 99%
“…With this in mind, and given our continued interest in oxidative sulfonamidation, 22–27 in this work we investigated the reactions of oxidative addition of sulfonamides RSO 2 NH 2 1a–k (R = CF 3 ) ( a ), 4-MeOC 6 H 4 ( b ), 4-MeC 6 H 4 ( c ), Ph ( d ), 4-ClC 6 H 4 ( e ), 4-BrC 6 H 4 ( f ), 4-NO 2 C 6 H 4 ( g ), 2-CF 3 C 6 H 4 ( h ), 4-CF 3 C 6 H 4 ( i ), NH 2 ( j ), Me ( k ) to camphene 2 in the presence of NBS, NIS, and t BuOCl/NaI in the solvents MeCN and CH 2 Cl 2 .…”
Section: Introductionmentioning
confidence: 99%